The Influence of Socialization and Making Ovitraps to Improve PKK Women's Knowledge of Dengue Prevention With Wolbachia - Mayadilanuari, Aerrosa Murenda; Nurvita, Silvia; Chotimah, Siti Noor; Sumantiawan, Dody Indra (Universitas Muhammadiyah Kalimantan Timur, 2024)
Dengue fever presents a critical health challenge in Semarang City, marked by a notable increase in cases and fatalities in recent years. Bandarharjo Subdistrict, located along the coast, is particularly vulnerable due to its susceptibility to high tides, which create stagnant water breeding grounds for Aedes aegypti mosquitoes, primary vectors of dengue. This study aimed to enhance dengue prevention knowledge among PKK women through Wolbachia-based strategies and ovitrap-making practice. This research was conducted in May 2024 and used a quasi-experimental design with 37 married women participating in pretest-posttest assessments. Results indicated a significant improvement in knowledge scores post-intervention (p-value < 0.001) among PKK women. The study highlights the urgent need for targeted community health interventions amidst rising dengue cases, underscoring the role of education and practical training in mitigating disease transmission. Future research should focus on longitudinal studies to assess the sustainability and broader public health impacts of Wolbachia-based interventions in endemic regions.